2007
DOI: 10.1016/j.juro.2006.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Features Associated With the Testicular Tumor of the Adrenogenital Syndrome

Abstract: In our series medical treatment failed in patients with testicular tumor of the adrenogenital syndrome and conservative surgical therapy was possible in select individuals. We identified special histopathological and immunophenotypic features, including synaptophysin staining, which distinguish testicular tumor of the adrenogenital syndrome from Leydig cell tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 15 publications
0
46
1
5
Order By: Relevance
“…Surgery is also suggested if an LC neoplasm is suspected, as the majority of LCT cases in this age group are benign. Few studies investigated immunohistochemical profiles of TART and LCT, and the currently available markers include synaptophysin, CD56 (both stronger in TART than in LCT) and the androgen receptor (absent in TART but positive in most cases of LCT) (24,25). A recent study, published after our study had been submitted for publication, investigated classical markers of steroidogenesis at mRNA level, and found most markers expressed in TART (10).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is also suggested if an LC neoplasm is suspected, as the majority of LCT cases in this age group are benign. Few studies investigated immunohistochemical profiles of TART and LCT, and the currently available markers include synaptophysin, CD56 (both stronger in TART than in LCT) and the androgen receptor (absent in TART but positive in most cases of LCT) (24,25). A recent study, published after our study had been submitted for publication, investigated classical markers of steroidogenesis at mRNA level, and found most markers expressed in TART (10).…”
Section: Discussionmentioning
confidence: 99%
“…TTAGS are bilateral in approximately 83% of cases, they are a benign sequel from an endocrine disease, and appear especially in younger patients [6], between 20 to 40 years old [2,6]. In macroscopic exams TTAGS are big multiple masses with "dark green" nodules, unlike LCT which are small, solid and yellow masses [1,2]. A study of TTAGS by Ashely and co [1], has provided useful microscopic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In macroscopic exams TTAGS are big multiple masses with "dark green" nodules, unlike LCT which are small, solid and yellow masses [1,2]. A study of TTAGS by Ashely and co [1], has provided useful microscopic characteristics. In this study, H & E staining revealed extensive fibrosis with adipose metaplasia in 56 to 78% of the cases of TTAGS, unlike LCT, were 0% showed these characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations